Polypharmacy among older Brazilians: prevalence, factors associated, and sociodemographic disparities (ELSI-Brazil) - Brayan V. Seixas; Gabriel R. Freitas (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: Polypharmacy has become an increasingly public health issue as population age and novel drugs are developed. Yet, evidence on low- and middle-income countries (LMIC) is still scarce. Objective: This work aims to estimate the prevalence of polypharmacy among Brazilians aged 50 and over, and investigate associated factors. Methods: A cross-sectional study was conducted using data from the baseline assessment of the Brazilian Longitudinal Study of Aging (ELSI-Brazil), a nationally representative study of persons aged 50 years and older (n=9,412). Univariate and bivariate analyses described the sample. Robust Poisson regression was used to estimate prevalence ratios and predict probabilities of polypharmacy. Results: Prevalence of polypharmacy was estimated at 13.5% among older adults in Brazil. Important disparities were observed in regard to gender (16.1% among women and 10.5% among men), race (16.0% among whites and 10.1% among blacks) and geographic region (ranging from 5.1% in the North to 18.7% in the South). The multivariate analysis showed that polypharmacy is associated with various sociodemographic/individual factors (age, gender, race, education, region, health status, body mass index) as well as with several variables of healthcare access/utilization (number of visits, same physician, provider's knowledge of patient's medications, gate-keeper, and difficulty managing own medication). Overall, the more utilization of health services, the higher the probability of polypharmacy, after adjusting for all other model covariates. Conclusions: Polypharmacy prevalence is relatively low in Brazil, compared to European countries. After controlling for variables of healthcare need and demographic characteristics, there is still substantial residual variance in polypharmacy prevalence. Policies to identify inappropriate prescribing and reduce regional discrepancies are necessary.